Implementing Kolcaba’s comfort theory for pain management in a patient with tongue cancer: A case report - Karisa, Putri; Fitria, Nita (The Journal of Palembang Nursing Studies, 2025)
Background: Tongue cancer is often associated with severe pain, further complicated when accompanied by comorbidities such as pulmonary tuberculosis. Persistent pain, worsened by continuous coughing, contributes to swallowing and speech difficulties, ultimately diminishing quality of life and resulting in poor prognosis. Objective: This case report aimed to explore the effectiveness of nursing care guided by Kolcaba’s Comfort Theory in alleviating pain in a patient with tongue cancer. Case Presentation: A 58-year-old man with tongue cancer, suspected lung metastasis, and pulmonary tuberculosis experienced severe chronic pain (VAS 9/10). Nursing care was structured according to Kolcaba’s framework, addressing physical, psychospiritual, environmental, and sociocultural comfort needs across the stages of relief, ease, and transcendence. Interventions included pharmacological therapy with morphine and non-pharmacological strategies such as foot massage and local honey application to the wound site. Pain was regularly assessed using the visual analog scale. Following interventions, the patient reported reduced pain intensity (VAS 7/10). Comfort levels improved, with physical comfort progressing from relief to ease, psychospiritual comfort from ease to transcendence, and environmental and sociocultural aspects maintained at the transcendence stage Conclusion: Nursing care based on Kolcaba’s Comfort Theory effectively contributed to pain reduction and enhanced comfort in this patient with tongue cancer. Integrating pharmacological and non-pharmacological interventions within a holistic nursing framework may offer practical strategies for managing complex cancer-related pain and improving quality of life.